2022
DOI: 10.3389/fimmu.2022.914108
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis to reveal potential therapeutic targets and prognostic biomarkers of skin cutaneous melanoma

Abstract: Skin cutaneous melanoma (SKCM) is a malignant tumor with high mortality rate in human, and its occurrence and development are jointly regulated by genes and the environment. However, the specific pathogenesis of SKCM is not completely understood. In recent years, an increasing number of studies have reported the important role of competing endogenous RNA (ceRNA) regulatory networks in various tumors; however, the complexity and specific biological effects of the ceRNA regulatory network of SKCM remain unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…also reported that there was a significant difference in hsa‐miR‐135a‐5p expression in the peripheral blood between lung cancer patients and healthy controls. In addition, hsa‐miR‐135a‐5p‐mediated ceRNA networks were also found to be related to the prognosis of skin cutaneous melanoma 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…also reported that there was a significant difference in hsa‐miR‐135a‐5p expression in the peripheral blood between lung cancer patients and healthy controls. In addition, hsa‐miR‐135a‐5p‐mediated ceRNA networks were also found to be related to the prognosis of skin cutaneous melanoma 22 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, hsa-miR-135a-5p-mediated ceRNA networks were also found to be related to the prognosis of skin cutaneous melanoma. 22 Research on ceRNAs in lung cancer will provide new insights into cancer pathogenesis and treatment options. 23 It has been suggested that lncRNAs can act as sponges with miRNAs to control the expression of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Thomas F Gajewski and colleagues reported that up to 90% of PTPRC+ cells produced CXCL10 transcripts, which played a critical role in recruiting effector CD8+ T cells to the tumor site ( 27 ). In 2022, Xiaobo Xia and colleagues reported that the OIP5-AS1-PTPRC/IL7R/CD69 axis in ceRNA as a clinical prognostic model ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous melanoma (CM) remains one of the most aggressive and deadliest forms of skin cancer, with epidemiological studies depicting the last few decades witnessing dramatic increases in incidences worldwide, with over 200,000 new cases diagnosed each year [ 1 , 2 ]. However, the morbidity and mortality rates of CM globally vary significantly, contingent on the availability of early screening and primary care [ 3 ]. This skin malignant tumor exhibits high metastasis, often leading to poor prognosis, as patients diagnosed with late-stage CM face a 5-year survival rate of less than 10% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%